An Economic analysis of the potential for precision farming in UK cereal production - Godwin, R. J.; Richards, Terence E.; Wood, G. A.; Welsh, J. P.; Knight, S. M. (Elsevier, 2003)
The results from alternative spatial nitrogen application studies are analysed in economic terms and compared to the costs of precision farming hardware, software and other services for cereal crops in the UK. At current prices, the benefits of variable rate application of nitrogen exceed the returns from a uniform application by an average of £22 ha−1 The cost of the precision farming systems range from £5 to £18 ha−1 depending upon the system chosen for an area of 250 ha. The benefits outweigh the associated costs for cereal farms in excess of 80 ha for the lowest price system to 200–300 ha for the more sophisticated systems. The scale of benefits obtained depends upon the magnitude of the response to the treatment and the proportion of the field that will respond. To be cost effective, a farmed area of 250 ha of cereals, where 30% of the area will respond to variable treatment, requires an increase in crop yield in the responsive areas of between 0·25 and 1.00 t ha−1 (at £65 t−1) for the basic and most expensive precision farming systems, respectively.
Keywords: Cereal production; Precision farming